The versatile utility of cysteine as a target for cancer treatment - Min, Jin-Young; Chun, Kyung-Soo; Kim, Do-Hee (Frontiers in Oncology, 2023)
Owing to its unique nucleophilicity, cysteine is an attractive sulfhydryl-containing proteinogenic amino acid. It is also utilized in various metabolic pathways and redox homeostasis, as it is used for the component of major endogenous antioxidant glutathione and the generation of sulfur-containing biomolecules. In addition, cysteine is the most nucleophilic amino acid of proteins and can react with endogenous or exogenous electrophiles which can result in the formation of covalent bonds, which can alter the cellular states and functions. Moreover, post-translational modifications of cysteines trigger redox signaling and affect the three-dimensional protein structure. Protein phosphorylation mediated by kinases and phosphatases play a key role in cellular signaling that regulates many physiological and pathological processes, and consequently, the modification of cysteine regulates its activities. The modification of cysteine residues in proteins is critically important for the design of novel types of pharmacological agents. Therefore, in cancer metabolism and cancer cell survival, cysteine plays an essential role in redox regulation of cellular status and protein function. This review summarizes the diverse regulatory mechanisms of cysteine bound to or free from proteins in cancer. Furthermore, it can enhance the comprehension of the role of cysteine in tumor biology which can help in the development of novel effective cancer therapies.